2011
DOI: 10.1002/dmrr.1258
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported lower respiratory tract infections and development of islet autoimmunity in children with the type 1 diabetes high‐risk HLA genotype: the MIDIA study

Abstract: Self-reported lower respiratory tract infections were associated with increased risk of islet autoimmunity in early infancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 11 publications
5
43
0
Order By: Relevance
“…This association indicates that RIEs are not a good predictor of whether an individual child will seroconvert for islet autoantibodies. However, at a population level, comparing groups with different RIE rates, the observed association is relatively consistent by country, remaining when adjusting for many other risk factors, and the association is in line with previous findings on type 1 diabetes [1, 47], which suggests a biological mechanism is probably present. Further research is required to understand whether the moderate effect of RIE on islet autoimmunity is due to the role of specific microbes or interactions with other unknown risk factors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This association indicates that RIEs are not a good predictor of whether an individual child will seroconvert for islet autoantibodies. However, at a population level, comparing groups with different RIE rates, the observed association is relatively consistent by country, remaining when adjusting for many other risk factors, and the association is in line with previous findings on type 1 diabetes [1, 47], which suggests a biological mechanism is probably present. Further research is required to understand whether the moderate effect of RIE on islet autoimmunity is due to the role of specific microbes or interactions with other unknown risk factors.…”
Section: Discussionsupporting
confidence: 89%
“…The present prospective study consisting of almost 8000 participants has confirmed the findings of two smaller prospective studies (the Norwegian MIDIA study with 885 participants and German BABYDIET study with 148 participants [4, 5]) of the risk association between respiratory infection and islet autoimmunity. The observed temporal pattern suggests an islet autoimmunity-triggering effect by respiratory infections.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results were once again heterogeneous, but studies in which the information on maternal smoking in pregnancy was registered before or soon after birth (rather than by retrospective recall) tended to be consistent with the initial observation by Dahlquist and Källén [76][77][78][79]. We identified published data from four birth cohort studies with longitudinal follow-up for islet autoantibodies [62,63,80,81]. While the total number of cases was only 244, and none of the studies showed significant associations, the point estimates for the relative risk appeared quite homogeneous at about 0.5 to 0.7.…”
Section: Caesarean Section Vs Notmentioning
confidence: 74%
“…Virus infections have long been considered as one of the most likely candidates because certain viruses are known to infect the pancreas and cause a T1D-like disease in animals [4,5]. Two recent studies have shown that respiratory infections precede the initiation of the b-cell damaging process in children who later progress to T1D [6,7]. One specific virus group, enteroviruses (EVs), has raised particular interest since it has been connected to T1D in numerous studies [4,5,8,9].…”
Section: Abstract: Antiviral Drugs • Enterovirus • Type 1 Diabetes • mentioning
confidence: 99%